Genetic liability to mental disorders in relation to the risk of hypertension - Huangfu, Ning; Lu, Yunlong; Ma, Hongchuang; Hu, Ziwei; Cui, Hanbin; Yang, Fangkun (Frontiers in Cardiovascular Medicine, 2023)
Background Observational studies have indicated that psychosocial factors contribute to hypertension; however, the causality of these associations remains unclear due to reverse causality and confounders. We aim to assess the causal associations of mental health disorders with hypertension. Methods Instrumental variables of anxiety disorder, attention deficit/hyperactivity disorder, autism spectrum disorder, depression, obsessive–compulsive disorder, post-traumatic stress disorder, schizophrenia, and subjective well-being measure were obtained from the corresponding largest genome-wide association studies. Summary statistics for the association of essential hypertension were obtained from the FinnGen Study (42,857 cases and 162,837 controls) and UK Biobank cohort (54,358 cases and 408,652 controls). The multiplicative random-effects inverse-variance weighted method was utilized as the primary analysis and three other statistical methods were conducted in the supplementary analyses. The results were combined using the fixed-effects method. Results In the pooled analyses, genetic liability to depression was associated with higher risk of hypertension (odds ratio [OR], 1.25; 95% confidence interval [CI], 1.17–1.35; p < 0.001). Besides, a suggestive association was found between genetically predicted higher weighted neuroticism sum-score and increased risk of hypertension (OR, 1.16; 95% CI, 1.02–1.33; p < 0.05). No associations were found for other mental health disorders. Sensitivity analyses revealed consistent evidence as the main results. Conclusion We provide consistent evidence for the causal effect of genetic liability to depression on hypertension, which highlights the importance of blood pressure measurement and monitoring in patients with depression.